Efeitos da dupla tarefa cognitivo-motora sobre a mobilidade funcional de longevos caidores e não caidores - Brauner, Fabiane de Oliveira (2019)
Cognitive-motor changes have an important contribution to mobility impairment in the elderly, which is usually followed by an increasing risk of falls. Oldest old are elderly people over 80 years of age, who, unfortunately, are more vulnerable to such events. In this context, the act of turning, due to its biomechanical characteristics, is known to increase susceptibility to postural instability. Although gait stability has been widely studied in the elderly, research on changes in nonlinear gait features among the oldest old is scarce. Moreover, regarding the history of fall, the predictive value of cognitive-motor performance while walking in the home environment in the oldest old is unknown. Therefore, the present study aims to evaluate the predictive capacity of the simple Timed Up and Go (TUG) and cognitive-motor TUG tests for the history of falls in the non-institutionalized oldest old. In this case-control study, the tests were carried out in the participants’ residences. Six valid attempts of the TUG test were performed, 3 in simple mode and 3 in DT, using the inertial sensor G-Walk and a smartphone Moto G5 to record the tests. The sample consisted of 60 oldest old subjects aged ≥85, from Porto Alegre, Rio Grande do Sul. Socio-demographic data, levels of physical activity, mental state, presence of depressive symptoms, concern about the occurrence of falls, medicine use, self-perception of functional balance and the functional scope test were also assessed using specific instruments. Descriptive statistics were used to characterize the sample. The TUG modalities (simple and TD) performance was compared using repeated measures ANOVA. Finally, the prediction of history of falls was assessed using binary logistic regression. All analyzes were performed in the SPSS 17.0 statistical package. The results showed that the elderly in this study, in general, were physically active and had no apparent changes in mental status. Whilst DT reduced the performance of the oldest old during the test, this TUG modality did not provide a greater predictive capacity to distinguish between fallers and non-fallers. However, the non-linear gait (turning 180º) was superior to the total TUG time for predicting the chance of falls, in both single and DT task. Finally, being physically active was the main independent protective factor to the occurrence of falls.